The Effectiveness of Madrasah Head Leadership, Work Ethics, and Internal Stakeholder Trust in Management of Tsanawiyah Madrasah, Deliserdang District, The Covid 19 Pandemic - Oda Kinata Banurea; Amiruddin Siahaan; Ramlan Padang; Roniah Situmorang; Yulinar Yulinar (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
This study aims to analyze the effectiveness of the madrasa principal's leadership, work ethics, and internal stakeholder trust in the management of Madrasah Tsanawiyah in Deli Serdang Regency during the Covid-19 pandemic. The technique used in the research uses descriptive, comparative and analytical qualitative research techniques from the results of field observation studies, documentation studies, interviews and triangulation so as to obtain data, original information, natural phenomenology on the actual research subject. The sample in this study was all the heads of public and private madrasah tsanawiyah as many as 130 head of madrasah tsanawiyah Deli Serdang district. The data analysis was carried out using content analysis, comparative and analysis from the results of the observation study documentation, triangulation interviews from the data obtained in the study. The results revealed that there was a decrease in the effectiveness of the leadership of the madrasa principal, work ethic, and the trust of stakeholders in the district of Deli Serdang during the pandemic. covid 19 by: 1. Madrasah principal decision makers are less democratic and less in favor of teachers; 2. Madrasah principals are less than ideal in dividing the proportion of working hours to teachers; 3. The principal of the madrasa does not maximize the supporting devices for online learning activities at school; 4. Not prioritizing services to students both online and directly coming to school; 5. The existence of madrasa activity programs that are not well implemented online or offline; 6. Inability of the head of madrasa to solve internal problems properly; 7, Lack of confidence that the head of the madrasa in carrying out his duties as a manager.